2011
DOI: 10.1029/2011jd016297
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution aerosol retrieval with MAIAC: Application to mountain regions

Abstract: [1] Aerosol spatial distribution in populated mountain areas is very heterogeneous and often characterized by scales of variability of several kilometers. Satellites provide an effective tool to map aerosols on an operational basis, but most of the aerosol products intended for continental/global applications have a coarse spatial resolution (10-18 km). The Multiangle Implementation of Atmospheric Correction (MAIAC) is a recently developed algorithm for the Moderate Resolution Imaging Spectroradiometer (MODIS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Several studies published in the last 3 years have shown that high spatial resolution is essential to detect spatial variability in PM levels [18] and in aerosol loadings at regional and at a sub-10 km scale (e.g. intra-urban domain) [19,20]. Our study using MAIAC data and mixed effect approach showed high accuracy in the New England domain thereby indicating that our model based on MAIAC data can be used to investigate the intra-urban exposure contrasts in PM 2 5 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies published in the last 3 years have shown that high spatial resolution is essential to detect spatial variability in PM levels [18] and in aerosol loadings at regional and at a sub-10 km scale (e.g. intra-urban domain) [19,20]. Our study using MAIAC data and mixed effect approach showed high accuracy in the New England domain thereby indicating that our model based on MAIAC data can be used to investigate the intra-urban exposure contrasts in PM 2 5 levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a new Multi-Angle Implementation of Atmospheric Correction (MAIAC) algorithm was developed for MODIS, which provides aerosol information at 1 km resolution (Lyapustin et al, 2011a, b). Emili et al (2011) evaluated MAIAC AOD in the European Alpine region and demonstrated its enhanced capabilities compared to the standard MODIS AOD product. Chudnovsky et al (2013) assessed the potential of the MAIAC AOD for examining the spatial patterns of PM 2.5 in the Boston metropolitan area (intra-urban scale, < 10 km) and parts of New England (regional scale).…”
Section: A Chudnovsky Et Al: a Critical Assessment Of High-resolutimentioning
confidence: 99%
“…This effect becomes particularly noticeable in rather pristine Alpine conditions with low average mid-visible aerosol optical thickness AOT ∼ 0.05-0.2. The problem of bias was successfully overcome by Emili et al (2011) with AOT data filtering where the main filter was based on the 3 × 3 pixel spatial variance test (σ ≤ 0.05). In more detail, this filter successively removed the highest AOT value from the 3 × 3 km 2 area if the standard deviation exceeded 0.05, and then averaged the remaining values effectively leading to 3 km resolution of the aerosol product.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, Emili et al (2011) evaluated MAIAC cloud/snow mask and aerosol products in the region of European Alps characterized by a heterogeneous aerosol distribution with strong impact of topography and aerosol sources localized in the narrow valleys with width of several km. While this study clearly demonstrated benefits of the high resolution data as compared to the standard 10 km MODIS product (Levy et al, 2007), including improved spatial coverage and 50 % increase in the number of observations, it has also revealed residual cloud and snow contamination.…”
Section: Introductionmentioning
confidence: 99%